PENURUNAN NYERI LUTUT LANSIA DENGAN KOMPRES AIR SEREI DI PANTI WREDHA DHARMA BHAKTI SURAKARTA - Erika Dewi Noorratri; Sri Hartutik (Jurnal Ilmu Keperawatan Komunitas, 2020)
Elderly is a part of the life process that cannot be realized and will be experienced by every individual in the world and is the final stage of the human life cycle. The various problems can arise in the aging process in the elderly. These problems include mentally, biologically, and economically. The Elderly who experience physical setbacks due to the aging process, such as pain can be reduced by compressing lemongrass. Many elderly people at Surakarta Dharma Nursing Home experience knee pain. The pain knee can be reduced by compressing lemongrass water. This study aimed to analyze the decrease in elderly knee pain by compressing lemongrass water in the nursing home of Dharma Bakti Surakarta. This research used. quasi experiment method.. The study design was pre-post group test design with control group. The research sample consisted of 18 treatment groups and 18 control groups. The result showed in the elderly treatment group from the first meeting to the sixth there was a significant decrease in knee pain, with a value of p = 0,000 (p <0.05). The lemongrass water compress treatment significantly reduced knee pain in the elderly, control treatments did not significantly reduce knee pain in the elderly and lemongrass water compress treatment was better in reducing knee pain in the elderly compared to controls. The lemongrass compress water treatment has a significant effect in reducing knee pain in the elderly.